Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Selectivity-based management for reversing overexploitation of demersal fisheries in North-western Mediterranean Sea - N. Bahamon; L. Recasens; J. Sala-Coromina; B. Calero; J.A. Garcia; G. Rotllant; A. Maurer; A. Rojas; L. Muth; J. Quevedo; M. Vigo; J. Ribera-Altimir; et al. (Marine Policy, 2024)

Population structure and reproductive patterns of the NW Mediterranean deep-sea macrourid Trachyrincus scabrus (Rafinesque, 1810) - U. Fernandez-Arcaya; L. Recasens; H. Murua; E. Ramirez-Llodra; G. Rotllant; J. B. Company (Marine Biology, 2012)

Otolith growth and age estimation in the European hake - B. Morales‐Nin; G. J. Tores; A. Lombarte; L. Recasens (Journal of Fish Biology, 1998)
The internal sulcal rings in Merluccius merluccius otoliths cannot be considered as annuli. In the absence of a strong seasonal Zeitgeber, hake otoliths in the Mediterranean did not lay down an interpretable ring pattern that would be useful for age determination. A total of 484 sagittal otoliths from specimens ranging between 6 and 94 cm L T was studied in monthly samples from the Gulf of Lions in 1989–1990. Transverse, burnt otolith sections was analysed with an image analysis system using enhanced and filtered images and using a fast Fourier transform (FFT) function to avoid subjectivity in ring interpretation. The otolith radius‐fish length relationship showed allometric growth and sexual dimorphism. The ring pattern was consistent for the sulcal rings in both sexes. Changes in the marginal increment showed the formation of multiple sulcal rings, of both environmental and physiological origin. The ring pattern depended on the sex and sexual activity.

Spatiotemporal variation in the population structure of the European hake in the NW Mediterranean - L. Recasens; A. Lombarte; B. Morales‐Nin; G. J. Tores (Journal of Fish Biology, 1998)
The bathymetric distribution of Merluccius merluccius was studied as a function of length, age and maturity of specimens caught by commercial trawl and longline in Different seasons. Males matured first at 28·8 cm (3 years old), and females at 38·0 cm (3·5 years old). Reproductive activity was noted practically throughout the year with its most pronounced spawning peak in the autumn. Most fish 46 cm were females. Specimens occurred between 50 and 750 m depth, although density was low at >400 m. Adults were found at all depth strata studied. Recruits and juveniles were limited to inshore waters